Rotation of the hammer and performance in hammer throwing - Huang, Jiaru; Peyré-Tartaruga, Leonardo A.; Lin, Junlei; Shi, Yu; Li, Wei (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: The purpose of this study was to determine the effects of hammer rotation on performance in hammer throwing.Methods: The hammer's velocity increment at different stages, the duration of rotations at different phases, and the horizontal azimuth angle and rotation radius at critical instants were calculated and compared between the long and short trials for 26 female athletes in actual competitions. Results: Compared to short trials, female throwers' long trials exhibited significantly larger release velocity (p < 0.001, ES = 1.42), greater velocity increment during the double support phase (p = 0.006, ES = 0.59), shorter duration during the single support phase (p ≤ 0.043, ES = 0.42-0.83), lower horizontal azimuth angle (p ≤ 0.027, ES = 0.46-0.57), and longer rotational radius at critical instants (p ≤ 0.021, ES = 0.48-0.73).Conclusion: During the process from the hammer head's low point to high point, athletes should focus on increasing the rotation radius of the hammer head and accelerating the right foot's landing speed during the single support phase. This approach aims to reduce the hammer's horizontal azimuth angle at the right foot touchdown, enhance the acceleration performance during the double support phase, and increase the release speed.